Reducing catheter-associated urinary tract infections in a large health system: a quality improvement approach using a fractal management system - Elie A. Saade; Esther J. Thatcher; Tina Lewis; Susan Carr; Marcia Cornell; Rachel Arnold; Zainab Albar; Peter Pronovost (Cambridge University Press, 2024)
Abstract Objective: Although preventable through established infection control practices, catheter-associated urinary tract infections (CAUTIs) remain prevalent in acute-care settings. Our goal was to improve the CAUTI rates through multiple hospitals through implementing sustainable practices, including enhancing communication, provider engagement, accountability, and transparency in reporting to achieve long-term improvements. Design: Quality improvement with multiple levels of interventions Setting: A health system in northern Ohio with 21 affiliated hospitals across 16 counties. Patients: Adult patients admitted to the hospital between June 2020 and June 2023. Methods: A broad set of quality improvement (QI) strategies was developed by an interdisciplinary team and guided by the Fractal Management System framework to ensure accountability, communication, and alignment across teams and facilities. Key drivers were indwelling urinary catheter (IUC) alternatives, insertion, maintenance, removal, and smart diagnostics. The main outcome measures were standardized infection ratios (SIR) and standardized utilization ratio (SUR), comparing period 1 (P1, June 2020 to December 2021) and period 2 (P2, January 2022 to June 2023). Results: Enhanced communication and management played crucial roles in minimizing IUC placement. Updated policies and protocols, coupled with clear guidelines and decision support tools, facilitated effective urinary management. Performance tracking and visual management boards provided real-time insights, while collaborative efforts, including staff huddles and multidisciplinary teamwork, ensured consistent adherence to best practices. Conclusions: A systemwide QI initiative focused on enhanced communication, management, and collaboration contributed to improved SIR and reduced CAUTI rates across multiple hospitals, highlighting the impact of strong communication and proactive management in healthcare settings.